Combination of minimum-maximum (m-m) attribute and zero-INTENS-difference (z-i-d) attribute for estimating below-tuning layer thickness : A new technique proposal - Purnomo, Eko Widi (2010)

(untitled)
Abstract- This paper demonstrates a new alternative way in estimating layer thickness below the tuning thickness of a poststacked,zero-phase seismic. Preliminary reflectivity map is built by band-pass filtering the amplitude map of the seismic. The filter removes the non minimum and or non maximum and left the maximum and or the minimum of seismic amplitude. The unresolved thickness below the tuning thickness is then corrected by zero-INTENS-difference (z-i-d) attribute, a form of spectral analysis of the seismic trace. z-i-d attribute is zero difference of Integrated Energy Spectra (INTENS) between a synthetic seismic and its true seismic. It has shown that, for free noise data and perfect wavelet, the z-i-d always point to true thickness. True layer thickness can be found by positioning the layer thickness to the z-i-d thickness accordingly The method has been applied successfully for wedge-modeled seismic with dominant frequency 20, 25 and 30Hz. With slightly difference approach, the method has been implemented for imperfect-wavelet synthetic seismic. Although, not as perfect as when implemented for perfect wavelet seismic, the method has given fairly good result when dealing with imperfect wavelet. The method performed good below tuning layer thickness estimation for modeled noisy seismic from noise level 5 and 10% but gives noisy result for seismic with 20% noise level.